Radio monitoring of the hard state jets in the 2011 outburst of MAXI J1836-194 - Russell, T.; Miller-Jones, James; Curran, Peter; Soria, R.; Altamirano, D.; Corbel, S.; Coriat, M.; Moin, A.; Russell, D.; Sivakoff, G.; Slaven-Blair, T.; Belloni, T.; et al. (Oxford University Press, 2015)
MAXI J1836−194 is a Galactic black hole candidate X-ray binary that was discovered in 2011 when it went into outburst. In this paper, we present the full radio monitoring of this system during its ‘failed’ outburst, in which the source did not complete a full set of state changes, only transitioning as far as the hard intermediate state. Observations with the Karl G. Jansky Very Large Array (VLA) and Australia Telescope Compact Array (ATCA) show that the jet properties changed significantly during the outburst. The VLA observations detected linearly polarized emission at a level of ~1 per cent early in the outburst, increasing to ~3 per cent as the outburst peaked. High-resolution images with the Very Long Baseline Array (VLBA) show an ~15 mas jet along the position angle −21 ± 2°, in agreement with the electric vector position angle found from our polarization results (−21 ± 4°), implying that the magnetic field is perpendicular to the jet. Astrometric observations suggest that the system required an asymmetric natal kick to explain its observed space velocity. Comparing quasi-simultaneous X-ray monitoring with the 5 GHz VLA observations from the 2011 outburst shows an unusually steep hard-state radio/X-ray correlation of LR∝L1.8±0.2X, where LR and LX denote the radio and X-ray luminosities, respectively. With ATCA and Swift monitoring of the source during a period of re-brightening in 2012, we show that the system lay on the same steep correlation. Due to the low inclination of this system, we then investigate the possibility that the observed correlation may have been steepened by variable Doppler boosting.